Recycling and Burial of Biogenic Silica in an Open Margin Oxygen Minimum Zone. Issue 2 (17th February 2021) - Dale, A. W.; Paul, K. M.; Clemens, D.; Scholz, F.; Schroller‐Lomnitz, U.; Wallmann, K.; Geilert, S.; Hensen, C.; Plass, A.; Liebetrau, V.; Grasse, P.; Sommer, S.
Abstract: An extensive data set of biogenic silica (BSi) fluxes is presented for the Peruvian oxygen minimum zone (OMZ) at 11°S and 12°S. Each transect extends from the shelf to the upper slope (∼1, 000 m) and dissects the permanently anoxic waters between ∼200 and 500 m water depth. BSi burial (2, 100 mmol m −2  yr −1 ) and recycling fluxes (3, 300 mmol m −2  yr −1 ) were highest on the shelf with mean preservation efficiencies (34% ± 15%) that exceed the global mean of 10%–20%. BSi preservation was highest on the inner shelf (up to 56%), decreasing to 7% and 12% under anoxic waters and below the OMZ, respectively. The data suggest that the main control on BSi preservation is the rate at which reactive BSi is transported away from undersaturated surface sediments by burial and bioturbation to the underlying saturated sediment layers where BSi dissolution is thermodynamically and/or kinetically inhibited. BSi burial across the entire Peruvian margin between 3°S to 15°S and down to 1, 000 m water depth is estimated to be 0.1–0.2 Tmol yr −1 ; equivalent to 2%–7% of total burial on continental margins. Existing global data permit a simple relationship between BSi rain rate to the seafloor and the accumulation of unaltered BSi, giving the possibility to reconstruct rain rates and primary production from the sediment archive in addition to benthic Si turnover in global models. Key Points: Biogenic silica (BSi) preservation is high on the shelf and low under predominantly anoxic bottom waters BSi burial across the Peruvian margin down to 1, 000 m water depth accounts for up to 7% of the global burial on continental margins Existing global data permit a simple relationship between BSi accumulation and rain rate